The color of stone : sculpting the black female subject in nineteenth-century America - Nelson, Charmaine (University of Minnesota Press, 2007)
In The Color of Stone, Charmaine A. Nelson brilliantly analyzes a key, but often neglected, aspect of neoclassical sculpturecolor. Considering three major worksHiram Powerss Greek Slave, William Wetmore Storys Cleopatra, and Edmonia Lewiss Death of Cleopatrashe explores the intersection of race, sex, and class to reveal the meanings each work holds in terms of colonial histories of visual representation.